A Quranic Concept with Universal Appeal : The Innate Monotheistic Disposition (Fitra) (Global Journal of Human-Social Science, 2023)
The aim of this article is to present some of the main issues relating to fitra - a term generally understood as designating an innate monotheistic disposition in humans - in the Qur an alone without any subsequent exegetical or traditional contribution1 On the other hand it gives pride of place to the intertextual approach which allows us to situate this notion in a thematic line going back to Ancient Greece and which gave rise to theories developed in various monotheistic circles of Late Antiquity particularly Jewish Judeo-Christian and Christian